Detection and Quantification of Histone H4 Citrullination in Early NETosis With Image Flow Cytometry Version 4 - Barbu, Emilia A.; Dominical, Venina M.; Mendelsohn, Laurel; Thein, Swee Lay (Frontiers in Immunology, 2020)
Neutrophil extracellular traps (NETs) formation has been implicated in an increasing number of infectious and non-infectious pathologies. NETosis is a tightly regulated process; the end-stage and read-out is the formation of DNA strands extruded from the nuclei, and traditionally assessed by fluorescence microscopy. As NETosis has emerged as a possible biomarker of the inflammatory process, there is a need for less time-consuming, consistent and quantitative approaches to improve its application in clinical assessment of pro-inflammatory conditions. Imaging Flow Cytometry (IFC) combines features of conventional flow cytometry with qualitative power of fluorescence microscopy and has an added advantage of the capability of assessing the early processes leading up to extrusion of the DNA-scaffolded strands. We explored the optimal imaging-based tools that can be used to measure citrullination of H4 in early NETosis. IFC identified and quantified histone 4 citrullination (H4cit3) induced with several known NETosis stimuli (PMA, LPS, hemin and IL-8) following treatment periods ranging from 2 minutes to 60 minutes. Its relationship with other alterations at nuclear and cellular level, such nuclear decondensation and super-condensation, multi-lobulated nuclei versus 1-lobe nuclei and cell membrane damage, were also quantified. We show that the early progress of the H4cit3 response in NETosis depends on the stimulus and identifies fast inducers (PMA), intermediate and slow (hemin and LPS); early IL-8-induced NETosis appears to be independent of histone 4 citrullination.